Enhancing farmers’ income by growing disease-free coconut - Hegde, Vinayaka; H, Pratibha V; Chowdappa, P (Indian Horticulture, 2018)
Coconut is counteracted by many diseases, some of which are lethal, while others are debilitating in nature. A brief account of the important diseases of coconut and their management practices are summarized in this article.